Chemical transformation of Ent-Kaurane-type diterpenoids from Croton tonkinensis Gagnep. I - Hydrolysis, acetylation, and oxydation of Ent-18-acetoxy-7beta-hydroxykaur-165-en- 15-one - Giang, Phan Minh; Hong Dung, Le Thi; Son, Phan Tong (Vietnam Journal of Chemistry, 2014)
In our studies on the phytochemistry and biological activities of Croton tonkinensis Gagnep. (Euphorbiaceae) oriented by traditional medicine interesting biological activities of the plant were demonstrated in correlation with the ent-kaurane-type diterpenoid constituents. The high accumulation of the active principle ent-18-acetoxy-7β-hydroxykaur-16-en-15-one (1) led to our recent study on the chemical modification of this lead compound. In this paper the transformations of 1 into several derivatives by hydrolysis, acetylation, and oxydation were reported. The cytotoxic activity against of the transformation products Hep-G2 and LU cells was evaluated.Keywords: Croton tonkinensis; Euphorbiaceae; ent-kaurane-type diterpenoid; chemical transformation; cytotoxicity.